Xanthan gum as an alternative to replace fat for coating and flavoring the extruded snacks - Graça, Carla (2021)
Food industries adapt their products and processes to the needs and desires of consumers. Extruded snacks include 10–20% fat sprinkled to fix flavors, seasonings, and salt. Considering the need to flavor snacks and simultaneously reduce the intake of calories, a polysaccharide is proposed in this study as a fat replacer. Impact of aqueous xanthan gum (Xg) solutions (0.25, 0.5, 1.0%) under two pH conditions (3.5 and 7.0) on structural and sensory characteristics of extruded snacks was analyzed. Rheological features of the coating solutions, as flow behaviour and viscoelastic profile (storage and loss moduli), were assessed. Texture analysis, to evaluate the snacks firmness and moisture content, water activity, retraction, and agglomeration index of the coated snacks, were also evaluated. Results for the aqueous Xg coatings were very encouraging showing good coating properties, not damaging the texture of the extrudates or causing agglomeration. Sensory analysis reflected a good overall acceptability of these snacks, as compared to oil-coated snacks. Therefore, xanthan gum should be used by the industry, to replace fat, on extruded snacks flavor coating solutions